Association between sleep duration and hypertension in southwest China: a population-based cross-sectional study - Chang, X; Chen, X; Ji, JS; Luo, G; Chen, X; Sun, Q; Zhang, N; Guo, Y; Pei, P; Li, L; Chen, Z; Wu, X (BMJ Publishing Group, 2022)
Objective Hypertension is a major risk factor and cause of many non-communicable diseases in China. While there have been studies on various diet and lifestyle risk factors, we do not know whether sleep duration has an association to blood pressure in southwest China. This predictor is useful in low-resource rural settings. We examined the association between sleep duration and hypertension in southwest China.